Empowering Youth in Islamic Philanthropy: Addressing Challenges and Enhancing Sustainable Engagement - Suryana, Yayan (Jurnal Sosiologi Reflektif, 2024)
Youth play a vital role in the sustainability of Islamic philanthropic organizations in Indonesia, serving as drivers, influencers, and beneficiaries. However, challenges such as career instability and limited understanding of Islamic philanthropy often hinder their long-term involvement in philanthropic activism. This study aims to analyze the strategic role of youth in Islamic philanthropic activism in Indonesia, identify the challenges they face, and explore solutions to enhance their sustainable engagement. The research employs a qualitative descriptive approach, examining three Islamic philanthropic organizations in Indonesia: Daarut Tauhiid (DT) Peduli, Dompet Dhuafa, and Rumah Amal Salman. Data were collected through observations and document analysis. The findings reveal that youth are significant in managing technology and social media-based philanthropic programs. They also act as influencers, encouraging other young people to participate in philanthropic activities. However, their status as volunteers, without stable career prospects, often results in temporary involvement. To promote more sustainable participation, institutional reforms are needed to provide professional development opportunities for youth in philanthropy. Kaum muda memiliki peran penting dalam keberlanjutan lembaga filantropi Islam di Indonesia, baik sebagai penggerak, influencer, maupun penerima manfaat. Namun, tantangan yang dihadapi kaum muda dalam aktivisme filantropi, seperti kurangnya stabilitas karier dan keterbatasan pemahaman tentang filantropi Islam, sering kali menghambat keterlibatan jangka panjang mereka. Penelitian ini bertujuan untuk menganalisis peran strategis kaum muda dalam aktivisme filantropi Islam di Indonesia dan mengidentifikasi tantangan yang dihadapi, serta solusi yang dapat diterapkan untuk meningkatkan keterlibatan mereka secara berkelanjutan. Metode penelitian ini menggunakan pendekatan deskriptif kualitatif dengan mengkaji tiga lembaga filantropi Islam di Indonesia: Daarut Tauhiid (DT) Peduli, Dompet Dhuafa, dan Rumah Amal Salman. Data dikumpulkan melalui observasi dan studi dokumentasi. Hasil penelitian menunjukkan bahwa kaum muda memiliki peran signifikan dalam pengelolaan program filantropi berbasis teknologi dan media sosial. Mereka juga berfungsi sebagai influencer untuk menarik generasi muda lainnya agar berpartisipasi dalam kegiatan filantropi. Namun, status mereka sebagai volunteer tanpa jaminan karier yang stabil membuat keterlibatan mereka dalam lembaga filantropi sering bersifat sementara. Untuk meningkatkan partisipasi yang lebih berkelanjutan, diperlukan reformasi sistem kelembagaan yang memungkinkan kaum muda berkembang secara profesional di dalam dunia filantropi.